Case Volume Analysis of Neurological Surgery Training Programs in the United States: 2017-2019. Issue 1 (5th February 2021) - Hopkins, Benjamin S; Shlobin, Nathan A; Kesavabhotla, Kartik; Smith, Zachary A; Dahdaleh, Nader S
ABSTRACT: BACKGROUND: Neurological surgery resident applicants seek out certain aspects of training, including case volume. While graduating Accreditation Council for Graduate Medical Education (ACGME) summary data are available yearly, they are not program specific and drawing conclusions is difficult. OBJECTIVE: To model general benchmarks for resident case volume across US programs to increase transparency and allow comparison of programs. METHODS: ACGME neurosurgical resident national reports from 2017 to 2019 were downloaded. Averages, standard deviations, and medians were recorded from each of the 27 procedural categories. Monte Carlo simulations were performed. Each distribution was run independently 1 to 4 times to represent the number of residents in a given program per year. Cases were divided into different categories: endovascular, open vascular, tumor, spine, and pediatrics. RESULTS: Average derived graduating case volumes were 1558 cases in 2017, 1599 cases in 2018, and 1618 cases in 2019. Programs with 3 residents per year averaged 4755 cases per year, with 90th percentile of 5401 cases per year. After removing endovascular cases, radiosurgery cases, and critical care procedures, the average was 3794 cases, with 90th percentile of 4197 cases per year. Categorically, the 90th percentile was 241 for open vascular, 373 for endovascular, 1600 for spine, 769 for tumor, and 352 for pediatrics. CONCLUSION: Case volume is an important part of neurosurgical training and a major factor in determining applicant residency program ranking. Through Monte Carlo simulation, the average case volume for programs with 3 residents per year was determined. Metrics and benchmarking remain an important part of applicant and program growth.